The Role of Social Media Marketing as an ICT Tool in Improving Supply Chain Sustainability of SMEs: A Systematic Literature Review - Ayokunmi, Lawal Abideen; Abu Seman, Noor Aslinda; Rashid, Umi Kartini; Mohamad, Arifha
The COVID-19 pandemic exposed significant communication issues within SMEs worldwide, revealing critical problems in their supply chains. This highlighted the importance of social media marketing as a crucial ICT tool for disseminating information and enhancing supply chain sustainability. SMEs, key drivers of economies in developing countries, often struggle with limited resources and information, hindering their sustainability efforts. Social media marketing offers an affordable and rapid communication channel for supply chain stakeholders, promoting sustainable practices. A systematic literature review (SLR) was conducted, analyzing 55 scholarly articles from 2016–2023, using databases such as Scopus, ScienceDirect, PubMed, and Web of Science. This SLR synthesizes existing studies on social media marketing and supply chain sustainability, identifying areas needing further research and offering recommendations for future studies and practical management. The study emphasizes the importance of social media marketing as a cost-effective platform for real-time information sharing and collaboration within the supply chain, which is critical for stability and sustainability, particularly during crises like COVID-19. This study offers researchers useful insights and practical suggestions for SME owner-managers on how to use social media marketing to improve environmental and social performance across the supply chain